Separation of Antibiotics Using Two Commercial Nanofiltration Membranes—Experimental Study and Modelling - Obinna Anike; Jiří Cuhorka; Nkechi Ezeogu; Petr Mikulášek (Membranes)
The widespread use of antimicrobial drugs has contributed to the increasing trace levels of contaminants in the environment, posing an environmental problem and a challenge to modern-day medicine seeking advanced solutions. Nanofiltration is one such breakthrough solution for the selective removal of antibiotics from wastewater due to their high efficiency, scalability, and versatility. This study examines the separation of antibiotics (sulfamethoxazole (SMX), trimethoprim (TMP), and metformin (MET), respectively) using commercially available membranes with an emphasis on AFC membranes (AFC 30 and AFC 80). Thus, we evaluate their efficacy, performance, and applicability in wastewater treatment processes. The data for characterizing the structural parameters of the NF membranes were determined from an uncharged organic solute rejection experiment, and the effect of various operating conditions on the retention of solutes was evaluated. All experimental data were collected using a laboratory-scale nanofiltration unit and HPLC, and rejection percentages were determined using analytical measurements. The results obtained allowed for the determination of the radius of the membrane pores using the Steric Hindrance Pore (SHP) model, resulting in values of 0.353 and 0.268 nm for the AFC 30 and AFC 80 membranes, respectively. Additionally, higher transmembrane pressure and feed flow were observed to lead to an increased rejection of antibiotics. AFC 30 demonstrated a rejection of 94% for SMX, 87% for TMP, and 87% for MET, while AFC 80 exhibited a rejection of 99.5% for SMX, 97.5% for TMP, and 98% for MET. The sieving effect appears to be the primary separation mechanism for AFC 30, as lower feed-flow rates were observed to intensify concentration polarization, thereby compromising rejection efficiency. On the contrary, AFC 80 experienced less concentration polarization due to its smaller pore sizes, effectively preventing pore clogging. Membrane performance was evaluated using the Spiegler–Kedem–Katchalsky model, based on irreversible thermodynamics, which effectively explained the mechanism of solute transport of antibiotics through the AFC 30 and AFC 80 membranes in the NF process.